Percepção de alunos sobre o ensino da ortodontia na graduação e na formação do clínico-geral - Maria Carolina Feio Barroso (2012)
The National Curriculum Guidelines (NCG) for university dentistry courses were created in Brazil in 2001 with the aim of standardizing teaching practices. These guidelines provided new recommendations to be adopted by all Higher Education Institutions (HIE). Orthodontics, which is a classic discipline in the area of dentistry, is covered by these guidelines. Despite this, orthodontics degree courses in Brazil display considerable variation in content, depending on the line of thought of the respective university. Teaching should provide a knowledge base so that the student can diagnose abnormalities in the dentures and deviations from standard growth patterns. However, the majority of orthodontics specialists believe that orthodontic treatment is a post-graduate subject and that undergraduates should merely observe the complexities of orthodontic mechanotherapy performed by a properly trained specialist. Others, however, believe that regular participation in the clinics of an orthodontic practice is the best way for the longitudinal observation of occlusion as it develops, and that general knowledge of the subject should have a strategic role in order to implement prevention, treatment or referral methods, if required. Studies of the quality of teaching of orthodontics in Brazil or which consider whether university courses meet educational goals are extremely rare. The aim of the present study was to consider whether university orthodontics courses contribute to the development of the general dental practitioner as proposed by the NCG. A quantitative exploratory cross-sectional study was performed of 225 undergraduate students at five dentistry colleges in the state of Minas Gerais, Brazil. A self-administered questionnaire with 36 open questions and one final closed question was used. The questions considered personal data (age, gender), course content (related to abilities and skills set out in the NCG), teaching methodology and skills acquired (measured by diagnostic and treatment decision making ability) and the intention to perform preventative and interceptive procedures, described here as autonomy. A total of 232 students returned 225 completed, valid questionnaires, with a non-response rate of 3.02%. Only 37.5% of students responded that they would perform an orthodontic procedure following graduation (autonomy). Skill acquired was associated with the option of performing orthodontic procedures during professional life, as well as the use of clinical case discussions by professors as teaching methodology (p0.05). The same results were not found for course content. Within the limitations of the present study, it can be concluded that the discipline of orthodontics in the undergraduate dentistry courses of the universities analyzed does not contribute fully to the training of a general dental practitioner in compliance with the recommendations of the NCG.